Terapi Akupresur dalam Keperawatan Holistik untuk Pemulihan Pasien Kritis di Unit Perawatan Intensif - Sohilait, Hana Priscilla Frudence; Nurul Safira Lahati (STIKES Suaka Insan, 2025)
Critically ill patients with various complications and symptoms that can affect their quality of life. Acupressure has garnered interest as a potential non-pharmacological adjunctive therapy to accelerate the recovery of critically ill patients in the ICU, a technique that nurses can perform. This study employed a scoping review methodology. Literature searches were conducted across leading medical databases, including PubMed, Science Direct, and ProQuest. Inclusion criteria comprised original studies, systematic reviews, and case reports published within the last five years. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The results show that various acupressure therapy methods used for critically ill patients with clinical conditions such as degenerative diseases and cardiovascular diseases, have the potential to reduce pain and anxiety, improve sleep quality, lower blood pressure, reduce nausea and vomiting, and enhance immune system function for ICU patients. This research aims to provide a foundation for integrating acupressure into holistic nursing care for critically ill patients, thereby improving both their quality of life and recovery.